Mass Balance and Yield Analysis of Apple (Malus sylvestris) Cider Drink Production in Batu City - Kumalasari, Dianita; Dewi, Dian Ayuning Puspa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Batu City is recognised as one of Indonesia's primary apple production centres, boasting significant potential for the development of fruit-based processed products. This study aims to analyze the mass balance and yield at each stage of the apple juice production process to obtain optimal production efficiency. The production process involves washing, crushing, filtering, mixing, cooking, and packaging. The mass balance was analyzed based on the principle of mass balance, while the yield was calculated from the ratio of output to input at each process stage. The results showed that the filtering process produced the lowest yield of 91.6% due to the waste of apple pulp, while the crushing and mixing process showed a yield of 100%. The mass balance calculation showed a match between the input and output masses at each process stage. This study emphasizes the importance of applying process engineering principles in food processing to increase efficiency, reduce material waste, and ensure production sustainability. Contribution to Sustainable Development Goals (SDGs):SDG 12-Responsible ConsumptionSDG 9-Industry, Innovation, and InfrastructureSDG 8-Decent Work and Economic GrowthSDG 2-Zero Hunger